Biofilmes de patógenos na indústria de alimentos: uma revisão sobre a sua formação e controle - Santana, Marcelo Felipe da Silva Estácio de (Universidade Federal de São Carlos, 2023)
Bacterial biofilms are sessile communities of bacteria, where a single or multiple species establish themselves on biotic or abiotic surfaces and become embedded in a self-produced polymeric material, bringing them greater resistance to adverse environmental factors. Biofilms represent a major challenge in the food industry, as they become sources of contamination causing health risks to consumers and great economic losses. Among the biofilm-forming microorganisms, there are important food-borne pathogens that cause diseases, which include Salmonella enterica, Clostridium perfringens, Escherichia coli, and others. With advances in studies on bacterial biofilms, including the expression of genes involved in this process, new mechanisms to control the formation of biofilms have emerged, including the use of chemical treatments, essential oils, enzymatic breakdown, and others. This work aimed to compile the characteristics and mechanisms used in the formation of biofilms of the main foodborne pathogens, in addition to presenting the general understanding of some strategies used in the food industries and their actions on the formation of biofilms.
Biofilms of pathogens in the food industry: a review on their formation and control
Keywords: Comunidades sésseis; Quorum sensing; Tratamentos antimicrobianos; Sessile communities; Antimicrobial treatments; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::CIENCIA DE ALIMENTOS::MICROBIOLOGIA DE ALIMENTOS